Removal of arsenic and silica from geothermal fluid by electrocoagulation. Issue 4 (August 2019) - Mroczek, E.K.; Graham, D.; Bacon, L.
Graphical abstract: Highlights: As(III) and silica are easily precipitated from geothermal with Fe electrodes. As is most efficiently co-precipitated with colloidal silica. Low initial pH resulted in faster coagulation and removal of both As and silica. Solids produced should not be disposed in landfills subject to acid generation. Abstract: In New Zealand and internationally, two deleterious constituents in geothermal fluids are silica and arsenic. Silica because scaling is a significant limiting factor for effective geothermal energy production and arsenic due to its potential groundwater contamination. Electrocoagulation treatment offers a simple and cost-effective method of removing both constituents, compared to the traditional treatment methods of coagulation and flocculation. It is an electrochemical process that uses direct current to remove a wide range of contaminants. This method has the potential to allow efficient downstream utilization of heat in low enthalpy fluids through cascaded direct use applications and can provide a more cost-effective disposal option than reinjection. Laboratory and field experiments have shown that the process can remove both silica and/or arsenic rapidly from aged geothermal water, leaving a floc which readily settles on standing. In aged water, iron electrodes were most efficient at reducing arsenic levels from approximately 4 mg L −1 to < 0.1 mg L −1, while aluminium electrodes were the most effective method for reducing silica levels from approximately 600 mg L −1 to < 100 mg L −1 . In a full-scale process, the silica and arsenic can be removed as two separate components, leaving an arsenic-free silica sludge to be disposed of in a landfill and a much smaller arsenic / iron fraction to be further treated or disposed of by reinjection.